Formation and development of the male copulatory organ in the spider Parasteatoda tepidariorum involves a metamorphosis-like process - Quade, Felix Simon Christian; Holtzheimer, Jana; Frohn, Jasper; Töpperwien, Mareike; Salditt, Tim; Prpic, Nikola-Michael; Justus Liebig University Giessen (My University, 2019)
Spiders have evolved a unique male copulatory organ, the pedipalp bulb. The morphology of the bulb is species specific and plays an important role in species recognition and prezygotic reproductive isolation. Despite its importance for spider biodiversity, the mechanisms that control bulb development are virtually unknown. We have used confocal laser scanning microscopy (CLSM) and diffusible iodine-based contrast-enhanced micro computed tomography (dice-microCT) to study bulb development in the spider Parasteatoda tepidariorum. These imaging technologies enabled us to study bulb development in situ, without the use of destructive procedures for the first time. We show here that the inflated pedipalp tip in the subadult stage is filled with haemolymph that rapidly coagulates. Coagulation indicates histolytic processes that disintegrate tibia and tarsus, similar to histolytic processes during metamorphosis in holometabolous insects. The coagulated material contains cell inclusions that likely represent the cell source for the re-establishment of tarsus and tibia after histolysis, comparable to the histoblasts in insect metamorphosis. The shape of the coagulated mass prefigures the shape of the adult tarsus (cymbium) like a blueprint for the histoblasts. This suggests a unique role for controlled coagulation after histolysis in the metamorphosis-like morphogenesis of the male pedipalp.
Keywords: ddc:570